Unravelling the cardio-renal-metabolic-foot connection in people with diabetes-related foot ulceration: a narrative review - Nick S. R. Lan; Girish Dwivedi; P. Gerry Fegan; Fran Game; Emma J. Hamilton (Cardiovascular Diabetology)
Abstract Diabetes-related foot ulceration (DFU), a serious but preventable complication of diabetes, is a leading cause of hospitalisation, lower extremity amputation and disability worldwide. People with DFU have a greater burden of cardiovascular risk factors, heart failure and chronic kidney disease, resulting in over two-fold higher risk of cardiovascular death compared with people with diabetes without DFU. Here, we propose a “cardio-renal-metabolic-foot” connection in people with diabetes based on shared pathophysiological mechanisms linking DFU with cardiovascular and renal disease. Whilst these mechanistic links remain to be fully elucidated, systemic inflammation and infection in the context of DFU are postulated as key mediators in the development, and progression of, cardiovascular and renal disease. However, cardiovascular and renal disease are also implicated in the pathogenesis of DFU, highlighting the multi-directional interplay between conditions. The impact of screening, prevention, and early management of cardiovascular complications associated with DFU requires further research. Multi-modality cardiac imaging could play a role in unravelling disease mechanisms leading to novel therapeutic strategies, as well as facilitating personalised risk assessment and management. Recent clinical trials have transformed the therapeutic landscape for people with type 2 diabetes, by demonstrating that sodium glucose co-transporter 2 inhibitors, glucagon-like peptide-1 agonists and non-steroidal mineralocorticoid receptor antagonists improve cardiovascular and renal outcomes. Although dedicated research in people with DFU is warranted, these therapies could target multiple facets of the “cardio-renal-metabolic-foot” connection. The holistic, person-centred approach to managing DFU should incorporate new multidisciplinary models of care focusing on the prevention and management of cardiovascular and kidney disease. Graphical abstract The cardio-renal-metabolic-foot connection in people with diabetes. There is a critical need for (1) a better understanding of mechanisms connecting DFU with cardiovascular and kidney disease, perhaps guided by cardiac imaging, novel biomarkers, multi-omics and artificial intelligence to facilitate current treatments and the development of novel therapeutic strategies, (2) more data from clinical trials, registries and biobanks to inform clinical guidelines and evidence-based medicine, and (3) health system-wide integration of structured models of care with a contemporary emphasis on cardio-renal-metabolic-foot health to improve patient outcomes. DFU diabetes-related foot ulceration. Created with BioRender.com